2000
DOI: 10.1074/jbc.m909746199
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Determinants by Which a Long Chain Toxin from Snake Venom Interacts with the Neuronal α7-Nicotinic Acetylcholine Receptor

Abstract: Venoms of elapid and hydrophid snakes contain a family of small toxic proteins called curarimimetic toxins or ␣-neurotoxins that bind with high affinity to muscular nicotinic acetylcholine receptors (AChRs) 1 and hence affect synaptic transmission (1, 2). All these toxins adopt a leaf-like shape with three adjacent loops rich in ␤-sheet that emerge from a small globular core where four disulfide bonds are invariably located (3-7). Notwithstanding their common fold and their similar biological function, ␣-neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
146
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 120 publications
(155 citation statements)
references
References 32 publications
7
146
0
2
Order By: Relevance
“…The C-terminal tail also stabilizes the complex but interacts only with residues at the receptor surface. Neither toxin loop I nor loop III interact with the receptor, which is in agreement with our mutational data (7). Although 75% of the surface of the toxin remains outside the complex, the buried surface is equal to 2,450 Å 2 , as observed for typical protein-protein interactions (23,24).…”
Section: Docking Of ␣-Cbtx On a Model Of ␣7supporting
confidence: 79%
See 4 more Smart Citations
“…The C-terminal tail also stabilizes the complex but interacts only with residues at the receptor surface. Neither toxin loop I nor loop III interact with the receptor, which is in agreement with our mutational data (7). Although 75% of the surface of the toxin remains outside the complex, the buried surface is equal to 2,450 Å 2 , as observed for typical protein-protein interactions (23,24).…”
Section: Docking Of ␣-Cbtx On a Model Of ␣7supporting
confidence: 79%
“…The others have not been tested (R68 and K69) or were insensitive to mutation (S31 and I32; ref. 7). Inspection of the structure of the complex showed that the average distances between side chain atoms of interacting residues globally agree with the energy values deduced from pairwise analyses.…”
Section: Docking Of ␣-Cbtx On a Model Of ␣7mentioning
confidence: 67%
See 3 more Smart Citations